PERENCANAAN MENINGKATKAN KETERAMPILAN MOTORIK HALUS ANAK MELALUI MEDIA PLASTISIN PADA ANAK KELOMPOK A1 DI RA SYIHABUDDIN KOTA MALANG - Desi Fitriani; Devi Wahyu Ertanti; Mutiara Sari Dewi (UNISMA, 2020)
Based on preliminary observations on Thursday, October 3, 2019 in RA Syihabuddin, Landungsari, Malang, that the fine motor skills of group A1 children have not yet been very developed. It is known that 7 out of 13 children are not yet skilled in using fine motor skills seen during cutting activities. So in this case, the researcher intends to conduct research, namely regarding activities using plasticine in improving children's fine motor skills, efforts to improve children's fine motor skills through plasticine media, and children's learning outcomes through activities by using plasticine of group A1 children in RA Syihabuddin. The purpose of this research is to describe activities using plasticine media in improving children's fine motor skills, efforts to improve children's fine motor skills through plasticine media, and children's learning outcomes through activities using plasticine media of children in group A1 in RA Syihabuddin.In this study, researchers used a qualitative approach and type of case study research. The source of the data obtained in this study is the primary data source. The primary data source obtained in this study is a written data source in the form of a structured interview guide sheet to the homeroom teacher RA Syihabuddin, Landungsari Malang. In this study, researchers collected data using interview techniques and then researchers analyzed the data qualitatively by following the concepts given by Kirk and Miller.In this study the results obtained from the statement of Mrs. Bint Khoirun Ni'mah which can be concluded that a PAUD / RA teacher must always be enthusiastic, cheerful when dealing with children and have a variety of creative ideas.